IDENTIFIKASI KONTAMINASI TELUR NEMATODA USUS PADA AYURAN KUBIS (Brassica oleracea) WARUNG MAKAN LESEHAN WONOSARI GUNUNGKIDUL YOGYAKARTA TAHUN 2010 - Nugroho, Cahyono; Djanah, Sitti Nur; Mulasari, Surahma Asti (Universitas Ahmad Dahlan, 2010)
Background : Vegetables can be eaten by fully or in portion on fresh condition (lalapan) or in be cooked. Fresh vegetables (lalapan) useful for the healthy of our bodies caused have good nutrition that relative high in vitamine and mineral shape, and one kind of thats vegetables is cabbage or kol. Cabbage which have been cleaned may still find the germs agent for example is the intestinal nematode. In Indonesia, intestinal nematode remain caused the serious public health problem, are Ascaris lumbricoides, hook worm and Trichuris trichiura. Soil, vegetables and water are the important one of the transmission way of the eggs of intestinal nematode, if there found many eggs of intestinal nematodes on the contamination sources (like vegetables, soil and the others) automatically will followed with the increasing of endemic degree.Method : This was descriptive qualitative research using laboratory enclosed. The cabbage that are used for examination materials, cabbage that usually use on food court especially pedestrian food court (warung makan lesehan) which sold on the midle of the city Wonosari Gunungkidul Yogyakarta. To make sediment of the eggs of intestinal nematode is used NaOH 0,2% solution as detergent solution. The practice of this exam use sedimentation technique and than be checked the diagnosting on microscope. The result of data that shown on therefore any contamination or yet the eggs of intestinal nematode, the kind of species of intestinal nematode and infective stage of those species. Data will be analyzed in descriptive qualitative statistic and been shown on table and chart.Result: The result of this research showed that there any contamination of the eggs of intestinal nematode from the cabbage (Brassica oleracea) that was been analyzed (38,89%), for the species of the eggs of intestinal nematode that shown positive samples are found Ascaris lumbricoides (50%), hook worm (12,5%) and Trichuris trichiura (37,5%). The infective stage that known is only one kind of infective stage that is an infective stage from Ascaris lumbricoides egg. Conclution: There was any contamination of the eggs of intestinal nematode on the cabbage (Brassica oleracea) that used for fresh vegetable menu (lalapan) on pedestrian food court in the midle of the city Wonosari Gunungkidul Yogyakarta. Keyword : Contamination, Cabbage (Brassica oleracea), The eggs of intestinal nematode.